Hyper-heuristics and fairness in examination timetabling problems - Muklason, Ahmad (2017)
Examination timetabling is a challenging optimisation problem in operations research and artificial intelligence. The main aim is to spread exams evenly throughout the overall time period to facilitate student comfort and success; however, existing examination timetabling solvers neglect fairness by optimising the sum or average of the objective function value without considering its distribution among students or other stakeholders. The balance between quality of the overall timetable and fairness (global fairness and within a cohort) is a major concern, thus the latter is added as a new objective function and quality indicator of examination timetables. The objective function is also considered from the perspectives of multiple stakeholders of examination timetabling (i.e. students, invigilators, markers and estates), as opposed to viewing the objective function as an aggregate function. These notions make the problem become a multi-objective optimisation problem.